2020
DOI: 10.1038/s41419-020-2484-2
|View full text |Cite
|
Sign up to set email alerts
|

CACNA1H downregulation induces skeletal muscle atrophy involving endoplasmic reticulum stress activation and autophagy flux blockade

Abstract: Multiple vaginal delivery (MVD) is an important factor for pelvic floor muscle (PFM) function decline and pelvic floor dysfunction (PFD). PFD is common in middle-aged and elderly women, but its pathogenesis is not clear. In this study, we found that the expression of CACNA1H was lower in the PFM of old mice after MVD compared with old or adult mice. In in-vitro studies, we found that treatment with the T-type Ca 2+ channel (T-channel) inhibitor NNC-55 or downregulation of the CACNA1H gene by siRNA intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 50 publications
2
16
0
Order By: Relevance
“…Previous study indicated compound heterozygous CACNA1H mutations might lead to severe congenital amyotrophy [61]. Another experimental analysis suggested reduced expression of CACNA1H related to multiple vaginal delivery is associated with muscular atrophy, indicating the key regulator role of CACNA1H in skeletal muscle function [62]. In our study, we found CACNA1H is interacted with G_Butyricicoccus and might affect HGS in UK Biobank samples.…”
Section: Discussionsupporting
confidence: 53%
“…Previous study indicated compound heterozygous CACNA1H mutations might lead to severe congenital amyotrophy [61]. Another experimental analysis suggested reduced expression of CACNA1H related to multiple vaginal delivery is associated with muscular atrophy, indicating the key regulator role of CACNA1H in skeletal muscle function [62]. In our study, we found CACNA1H is interacted with G_Butyricicoccus and might affect HGS in UK Biobank samples.…”
Section: Discussionsupporting
confidence: 53%
“…Mouse model of visceral hypersensitivity and in irritable bowel syndrome [ 272 ]. Mouse model of inflammatory and neuropathic pain [ 273 ] (2S)-6-prenylnaringenin can block Cav3.2 current [ 150 ] Apoptotic pathway in myocardial cells [ 155 ] Autophagy pathway [ 158 ] CACNA2D1 Calcium voltage-gated channel auxiliary subunit alpha2delta 1 Cav1.3 L-type None Conventional knockout mouse using a construct targeting exon 2 of alpha (2)/delta-1 [ 274 ]. α2 δ1 Tg model for neuropathic pain [ 275 , 276 ] None None CACNA2D2 Calcium voltage-gated channel auxiliary subunit alpha2delta 2 Cav1.3 L-type None The “ducky’ du (2 J) mouse model of ataxia and absence epilepsy [ 277 ].…”
Section: Resultsmentioning
confidence: 99%
“…Induced pluripotent stem cells (iPSCs) and HEK293T cells for spinocerebellar ataxia [ 302 ] Endostatin, zonisamide, clozapine, roscovitine, mibefradil, iron and zinc can block Cav3.1 channel [ 179 185 ] Dearomatized isoprenylated acylphloroglucinol and monoterpenoid, hypatone A could rescue pathological gating properties for spinocerebellar ataxia 42 [ 186 ] Autophagic pathway in melanoma cells [ 198 ] Apoptotic pathway in [ 193 – 195 ] Ras-ERK signaling pathway [ 200 , 201 ] CACNA1H Calcium voltage-gated channel subunit alpha1 H Cav3.2 T-type None TsA-201 cell for amyotrophic lateral sclerosis [ 303 ] KYS-05090S can block Cav3.2 current [ 187 ] Apoptotic pathway in myocardial cells [ 155 ]. Autophagy pathway [ 158 ] CACNA1I Calcium Voltage-Gated Channel Subunit Alpha1 I Cav 3.3 T-type HEK293T and mouse chromaffin cells for ID and epilepsy [ 74 ] None Zinc modulates Cav3.3 channel gating [ 181 ] None CACNA2D1 Calcium voltage-gated channel auxiliary subunit alpha2delta 1 Cav1.3 L-type None MKN74 cells (human gastric cancer cell line) [ 190 ] MicroRNA-107 can inhibit expression of Cav1.3 in cancer [ 188 , 189 ] Amlodipine can block Cav1.3 in cancer [ 190 ] CXCR3/ERK1/2 signaling pathway [ 203 ] Ras/Raf/MEK/ERK signaling pathway [ 202 ] …”
Section: Resultsmentioning
confidence: 99%
“…ER proteostasis surveillance mediated by ERS also plays a crucial physiological role in the maintenance of skeletal muscle and is emerging as a possible driver of cell apoptosis. Our previous study uncovered that TCC inhibition induced C2C12 myotube atrophy through ERS activation and autophagy flux blockade [24]. ERS is upstream of autophagy blockade induced by NNC‐55, and mitochondrial dysfunction could also regulate autophagic process through ROS production and mitochondria‐specific proteins.…”
Section: Discussionmentioning
confidence: 99%
“…We previously identified that the expression of TH ( CACNA1H ) is higher than that of the other two types in mammalian skeletal muscle and myoblasts. TCC inhibition by NNC 55‐0396 hydrate (NNC‐55) promoted ERS activation and autophagosome formation but blocked distal autophagy and autophagy flux [24]. Given that ERS is upstream of autophagy blockade induced by NNC‐55 and mitochondrial dysfunction could regulate autophagic process through ROS production and mitochondria‐specific proteins [25], we explore the primary effects of TCC function loss on ERS activation and mitochondrial‐related apoptosis.…”
mentioning
confidence: 99%